Probiotic Meat Products and Nutrition - Sena Özbay Doğu; Cemalettin Sarıçoban (Turkish Journal of Agriculture: Food Science and Technology)
Meat and meat products are the basic building blocks of nutrition and are recognized as good sources of high biological value proteins, group B vitamins, minerals as well as some other bioactive compounds. The trend today is the development of novel food for special health use, called functional food, to promote human health and well-being of consumers. The trends are based on either reducing the content of unhealthy substances (like salt) or improving the content of substances with healthy benefits (like probiotics). Thus, it may also change the perspective of consumers towards meat products which associated with coronary artery disease. Meat is an ideal structure for probiotic microorganisms. Probiotic meat products are obtained by addition of probiotic to fermented meat products. These probiotic meat products are offered both healthy and improved taste and flavor, but also as safe food to consumer. Thus, when these probiotic meat products ensure flavor and nutritional to consumers, additionally they have a positive impact on their health.